2016
DOI: 10.4081/jlimnol.2016.1369
|View full text |Cite
|
Sign up to set email alerts
|

Demography and feeding behavior of Stenostomum leucops (Dugés, 1828)

Abstract: Freshwater

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
(48 reference statements)
1
1
0
Order By: Relevance
“…In nature, small prey including protozoans and rotifers are probably consumed more than cladocerans. Núñez-Ortiz et al [ 38 ] showed a preference for rotifers in the small Stenostomum leucops as well, with a functional response close to that here found for M . craci .…”
Section: Discussionsupporting
confidence: 86%
“…In nature, small prey including protozoans and rotifers are probably consumed more than cladocerans. Núñez-Ortiz et al [ 38 ] showed a preference for rotifers in the small Stenostomum leucops as well, with a functional response close to that here found for M . craci .…”
Section: Discussionsupporting
confidence: 86%
“…This supports our hypothesis that a few environmental variables (pH, dissolved oxygen) would be good predictors of the presence of Collothecidae in Lake Xochimilco. Biotic interactions were not considered here, but some small periphytic metazoans such as amebas, turbellarians, snails, and predatory rotifers such as Acyclus , Aspelta , Asplanchnopus , Dicranophorus , and Eosphora may influence the population densities of sessile rotifers (Aloi & Brönmark, ; Han, Wang, Lin, & Dumont, ; Núñez‐Ortiz, Nandini, & Sarma, ; Sládeček, ). Some of these species are predatory, but they may also simply dislodge sessile rotifers from their substratum (e.g., snails).…”
Section: Discussionmentioning
confidence: 99%